Isomorphic pressures influencing the level of mandatory disclosure within financial statements of Indonesian local governments - Arifin, Johan (Curtin University, 2014)
Using isomorphic institutional theory this study examines the level of mandatory disclosure within financial statements of Indonesian local governments. There is a moderate level of compliance with key mandatory disclosures (69.6%). The highest level is on issues relating to Financial Statement Items (91.7%) whereas the lowest level is for Non-Financial Information (44.7%). Java/non-Java jurisdiction, presence of an assistance and training programme, and proportion of non-supporting parties are significant predictors of the level of mandatory disclosure.